PRINCIPLES AND METHODS FOR THE MANAGEMENT AND REGULATION OF FINANCES IN ISLAM: AN APPROACH TO MAULANA ASHRAF ALI THANAVI - Rashid, Burhan (International Journal of Islamic Banking and Finance Research, 2022)
In light of Maulana Ashraf Ali Thanavi’s discussions and deliberations, the purpose of this study is to analyze the principles and methods for financial management in Islam, with a focus on three essential areas of finance: obtaining wealth, securing wealth, and spending wealth. For this aim, several of M. Thānavī’s written works were searched, and his discussions on Islamic economic teachings were collected and expanded upon, and references to all primary and secondary sources were provided. The entire content is presented here in a systematic and academic manner, culminating in a five-point conclusion. The findings show that the state of contentment in economic and financial concerns is the result of complete trust in God, the Creator and the Provider of all creatures, as well as belief in the Day of Judgment. This state of contentment and confidence is attained through practical measures such as avoiding extravagance, squandering, and ostentation while adopting a balanced and moderate lifestyle. Similarly, the data reveal that adhering to business ethics outlined in the Sharī‘ah ensures a safe, peaceful, and prosperous individual and communal existence, and bring about abundant barakah (benediction). The current paper will thus serve as a compendium of Islamic economic and financial teachings, as well as related moral and ethical precepts. JEL Classification Codes: A130, G41, G51.